52.1: Invited Paper: High Performance Metal‐Oxide TFT on Flexible Plastic Substrates. Issue 1 (1st July 2013) - Shieh, Chan‐Long; Wang, Guangming; Musolf, Juergen; Foong, Fatt; Xiao, Tian; Yu, Gang
Abstract: Active Matrix displays on light weight, non‐fragile, plastic substrates are of great interests for portable applications. One of the challenges has been device performance processed at low temperature: in both carrier mobility and operation stability. Another challenge has been a TFT process flow without rigorous alignment among patterns in different layers. In this presentation, we present a MOTFT processed at low temperature, on PEN or PET substrates, with mobility above 50 cm 2 /Vsec and with bias stability sufficient for portable display products. TFT performance over large substrate size are guaranteed by a proprietary self‐aligned process which enables large size display backpanel be made in roll‐to‐roll process with a flexible substrate.